Exacerbation model of cumulative adverse experiences: prevalence, characteristics, and risk factors of self-harm and suicidality among Chinese migrant workers - Jiayi, Tang; Wang, Mengting; Fang, Juan; Jian, Wenqian; Pan, Hong; Hu, Xinyu; Liu, Yanlong; Chen, Li; Liu, Linhui (Frontiers in Public Health, 2025)
BackgroundSelf-harm and suicidality represent critical public health issues, particularly among migrant workers in China, who often confront adverse living and working conditions. This study aimed to investigate the prevalence and characteristics of self-harm and suicidality, explore the risk factors associated with adverse childhood experiences (ACEs) and adverse adulthood experiences (AAEs), and elucidate the relationship models between cumulative risk factors and self-harm and suicidality among Chinese migrant workers.MethodsWe conducted a cross-sectional survey involving 2,739 rural-to-urban migrant workers across China. Participants completed a structured questionnaire assessing self-harm, suicidality, ACEs, AAEs, and sociodemographic characteristics. Data analysis involved descriptive statistics, cross-tabulation, independent samples t-tests, logistic regression, and stepwise regression.ResultsAmong the participants, the prevalence of self-harm and suicidality was 12.6 and 10.4%, respectively. Both ACEs and AAEs showed significant associations with self-harm and suicidality. Individuals reporting ACEs, such as parental divorce, childhood exposure to community violence, and school dropout, as well as AAEs including adult poverty, divorce intention, parent–child conflict, work burnout, and workplace discrimination, exhibited increased tendencies toward self-harm and suicidality. Moreover, a significant positive correlation was found between the cumulative risk index and self-harm and suicidality among Chinese migrant workers, with a critical threshold identified at 4–5 risk factors, indicating an exacerbation model.ConclusionThis study underscores the high prevalence of self-harm and suicidality among Chinese migrant workers, highlighting the significant impact of cumulative ACEs and AAEs on these outcomes. The findings emphasize the necessity for targeted interventions that address the identified risk factors to enhance the mental health and well-being of this vulnerable population.